THE USE OF DUBBING MUTED ANIMATION MOVIE CLIP TECHNIQUE TO IMPROVE THE ENGLISH-SPEAKING SKILL OF KIDS ENGLISH COURSE PARTICIPANTS - Ariani Ariani; Syarifuddin Dollah; Andi Anto Patak; Fitriani Fitriani (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This classroom action research aimed to examine the effectiveness of the dubbing muted animation movie clip technique in improving the English-speaking skills of students in the Upper Intermediate Kids Class at GRACE English Course. The study was conducted in two cycles, involving 12 students, through the implementation of dubbing activities using selected animated clips. Data were collected through speaking tests that assessed pronunciation, intonation, fluency, accuracy, and vocabulary. The findings revealed a significant improvement in students' speaking skills across all assessed aspects. The mean speaking score increased from 71.58 in the pre-research phase to 93.80 in the second cycle. Moreover, the t-test result (19.16 > 2.608) confirmed the statistical significance of this improvement. These results suggest that the dubbing technique creates an engaging, low-anxiety environment that supports speaking practice through mimicry, repetition, and contextualized interaction, making it an effective pedagogical strategy for enhancing young learners’ oral English proficiency.